60th birthday of Mykhailo Tokarchuk (Condensed Matter Physics, 2016)
The development of nonequilibrium statistical theory in Ukraine during the last several decades is indubitably associated with the name of Professor Mykhailo Tokarchuk, a prominent scientist who celebrates these days his 60th anniversary.